PENGARUH KUALITAS PRODUK SUSU FRISIAN FLAG TERHADAP KEPUASAN KONSUMEN DI PT. TRIYANTO SUKSES MANDIRI (TERLAKSANA GROUP) GEDEBAGE BANDUNG - Sa'ad Noor; Dwi Utami (Jurnal Co Management, 2019)
This research is intended to obtain product quality data and customer satisfaction data at PT Triyanto Sukses Mandiri (Terlaksana Group) Gedebage Bandung. As for the purpose of this study is to find out whether there is an influence between product quality and customer satisfaction at PT. Triyanto Sukses Mandiri (Terlaksana Group) Gedebage Bandung. The research method used was descriptive quantitative method. Data was taken using research instruments in the form of questionnaires distributed to 54 consumers randomly. Data collection results were processed and analyzed using Pearson Product Moment correlation analysis techniques carried out with the SPSS V.20. From the results of processing and analyzing data, it is found that thitung is 6.272 while t table 1.67469 means that thitung is greater than ttabel (6.272> 1.67469). This shows that product quality has a positive and significant effect on customer satisfaction, classified as a strong classification. The coefficient of determination (r2) is 43.1%, which means that customer satisfaction is influenced by product quality of 43.1%. In addition to the correlation analysis above the researchers carried out descriptive statistical analysis of the two research variables (variables X and Y). From the results of the analysis the researchers got a picture that the Product Quality variable (Variable X) which was responding with the lowest value was sub. X.2) with an average value of 3.31 while the sub-variable that gets the highest rating is sub- product durability variable (X.4) with an average value of 3.61.As for the results of the analysis of the Consumer Satisfaction variable (Y variable) the researcher gets a picture that the sub-variable that is responded to with the lowest value is sub-variable customer satisfaction with Special Features (Y.2) with an average value of 3.28, while sub.variable customer satisfaction that gets the highest value is employee satisfaction in getting service (Y.4) with an average value of 3.50. Based on the results of the above analysis, the researcher advises companies to continue improving the quality of their products (variable X), especially in terms of product reliability (X.2) so that customer satisfaction can be maintained and improved again.